2021
DOI: 10.1073/pnas.2025899118
|View full text |Cite
|
Sign up to set email alerts
|

Warm nights disrupt transcriptome rhythms in field-grown rice panicles

Abstract: In rice, a small increase in nighttime temperature reduces grain yield and quality. How warm nighttime temperatures (WNT) produce these detrimental effects is not well understood, especially in field conditions where the typical day-to-night temperature fluctuation exceeds the mild increase in nighttime temperature. We observed genome-wide disruption of gene expression timing during the reproductive phase in field-grown rice panicles acclimated to 2 to 3 °C WNT. Transcripts previously identified as rhythmicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 119 publications
0
22
0
Order By: Relevance
“…While nighttime temperature increases are less common in natural settings on an acute scale, more land area has experienced asymmetric nighttime versus daytime warming globally (from 1983 to 2017; Cox et al, 2020 ). Warmer night temperatures (2°C–3°C increase) led to a 12.5% reduction in grain yield and altered global temporal transcriptional patterns in field-grown rice panicles, with circadian and diel rhythmic genes most sensitive to the warmer nights ( Desai et al, 2021 ). The time of day when temperature fluctuations occur on both daily and seasonal scales is relevant when considering the impact of temperature variation and climate change on clock function and plant growth and performance.…”
Section: Role Of the Clock In Temperature Perception And Signalingmentioning
confidence: 99%
“…While nighttime temperature increases are less common in natural settings on an acute scale, more land area has experienced asymmetric nighttime versus daytime warming globally (from 1983 to 2017; Cox et al, 2020 ). Warmer night temperatures (2°C–3°C increase) led to a 12.5% reduction in grain yield and altered global temporal transcriptional patterns in field-grown rice panicles, with circadian and diel rhythmic genes most sensitive to the warmer nights ( Desai et al, 2021 ). The time of day when temperature fluctuations occur on both daily and seasonal scales is relevant when considering the impact of temperature variation and climate change on clock function and plant growth and performance.…”
Section: Role Of the Clock In Temperature Perception And Signalingmentioning
confidence: 99%
“…Even if this observation is broad and conservative in other vegetable crops, how to balance yield and quality still needs to be considered. In addition, a small increase in nighttime temperature destroys the tight temporal coordination between internal molecular events and the environment, thus reducing grain yield and quality [ 63 ], suggesting that an appropriate diurnal temperature difference is conducive to the normal growth and development of plants. This facilitates the accumulation of nutrients and the reduction of respiratory expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…Responses to any additional perturbations, such as environmental stressors, must be invoked on this underlying, dynamic transcriptional landscape ( Greenham and McClung 2015 ; Bonnot and Nagel 2021 ). Studies in poplar ( Wilkins et al 2009 ; Hamanishi et al 2010 ; Raj et al 2011 ), Arabidopsis ( Wilkins et al 2010 ; Dubois et al 2017 ; Blair et al 2019 ) and rice ( Oryza sativa ) ( Wilkins et al 2016 ; Grinevich et al 2019 ; Desai et al 2021 ) have shown that transcriptional responses to stress are different at different times of day. This was consistent with our findings here that the majority of drought-responsive genes had distinct expression profiles in the morning and early evening.…”
Section: Discussionmentioning
confidence: 99%